The Meluḫḫa Village. Evidence of Acculturation of Harappan Traders in Late Third Millennium Mesopotamia - Parpola, Simo
criticism of D. O. Edzard: 164f.; Ur III texts Delaporte, ITT IV No. 7137; Lau, OBTR No. 242; CT 5 pl. 36f.; Chiera, STA No. 19; Pinches, Amherst No. 54; Barton, HLC III No. 368; CT 3 pl. 17; Reisner, TUT No. 154; de Genouillac, ITT II 705; Lutz, UCP 9/2 No. 65; Delaporte, ITT IV 8015; Thureau-Dangin, ITT I 1426; (Sargonic) CT 50 No. 76.